IMPLEMENTING THE BREAD-MAKING INDEPENDENCE PROGRAM TO FOSTER INMATES’ ENTREPRENEURIAL SPIRIT AT KENDARI CLASS IIA CORRECTIONAL FACILITY - Putra Hadini, La Ode M Aldhian; Soge, Markus Marselinus (Universitas Nusa Cendana, 2026)
This research examines the implementation of a bread-making independence development program at Class IIA Kendari Correctional Institution as an effort to foster the entrepreneurial spirit of inmates. The study is motivated by the need to equip inmates with practical work skills and an entrepreneurial mindset that can support their social reintegration after completing their sentences. The research aims to analyze how the program contributes to developing entrepreneurial values among inmates and to identify the challenges encountered during its implementation. The study employs a qualitative descriptive approach, with data collected through observation, interviews, and documentation. The analysis is based on the implementation theory of David C. Korten and the entrepreneurship perspective of Purnomo. The findings indicate that the bread-making program helps improve inmates’ entrepreneurial skills through practical training, talent development, and cooperation with external partners. However, the implementation still faces several obstacles, including limited facilities, insufficient training materials, and restricted participation opportunities for inmates. Despite these challenges, the program has the potential to support inmates in developing productive skills that can be utilized after their release. Keywords: Implementation; Entrepreneurship; Development; Inmates; Bread